Narrative Review on Universal Health Coverage in Thailand and China from the Lens of Social Determinants of Health Theory - Kang, Yiting; Suphanchaimat, Rapeepong; Wongsuwanphon, Saruttaya (Outbreak, Surveillance, Investigation & Response (OSIR) Journal, 2024)
This article through the literature review method briefly compares universal health coverage (UHC) in Thailand and China, highlighting their strategies and challenges in achieving UHC through the lens of social determinants of health: a) health financing design and sustainability, b) accessibility of healthcare resources, and c) participatory and responsive governance. While Thailand mainly utilizes a tax-based approach, China employs a health insurance model. Both countries have achieved high insurance coverage. However, some challenges exist. The unmet need for health services due to long waiting times has been a key concern in Thailand, whereas financial hardship from receiving care was a critical concern in the case of China. Thailand has created a mechanism to allow a wide range of stakeholders to participate in the UHC design to ensure responsive governance. In contrast, China has not yet formed comprehensive legal grounds for participatory and responsive governance on UHC. Their experiences and encountered obstacles can offer valuable lessons on how middle-income nations can advance towards UHC, highlighting the critical need for ongoing improvements in health systems to tackle the existing and new health challenges due to the change in population demographics and the continuing increase of population healthcare demand.